An egg for everyone: Pathways to universal access to one of nature's most nutritious foods - Morris, Saul S.; Beesabathuni, Kalpana; Headey, Derek (Maternal and child nutrition, 2018)
Eggs are a highly nutritious food but have been shown to be infrequently consumed in many low‐income countries, especially by women and children. We collate country‐level data on egg production, availability, consumption, prices, industry structure, and contextual trends and use these to estimate current patterns and likely future outcomes under four alternative scenarios. These scenarios are as follows: incremental change based on expected economic growth and urbanisation (the base scenario); enhanced productivity of independent small producers; aggregated production in egg hubs; and the accelerated spread of large‐scale intensive production. All scenarios are modelled out to 2030 using a mix of regression and deterministic models. We find that children's consumption of eggs is highly correlated with national availability, and both are a function of egg prices. Eggs are unavailable, expensive, and infrequently consumed by children in much of South Asia and sub‐Saharan Africa. The base scenario results in modest increases in production in low‐income regions. Focusing efforts on independent small producers can only boost rural consumption in a handful of countries where poultry ownership is unusually high and would be expensive and logistically challenging to scale. Aggregation of production, with minimum flock sizes of 5,000 layers per farm, is a more promising pathway to increasing availability in rural areas. To meet the needs of urban populations, large‐scale intensive production is needed. Intensive production brings down prices significantly, allowing many more poor households to access and consume eggs. Recent experience in countries such as Thailand confirms that this is both feasible and impactful.